Improved one-dimensional model of piezoelectric laminates for energy harvesters including three dimensional effects. (1st September 2015) - Gafforelli, Giacomo; Ardito, Raffaele; Corigliano, Alberto
Abstract: The application of piezoelectric composites in energy harvesters is continuously increasing even at the microscale, with the immediate corollary of a fundamental need for improved computational tools for optimization of performances at the design level. In this paper, a refined, yet simple model is proposed with the aim of providing fast and insightful solutions to the multi-physics problem of energy harvesting via piezoelectric layered structures. The main objective is to retain a simple structural model (Euler–Bernoulli beam), with the inclusion of effects connected to the actual three-dimensional shape of the device. A thorough presentation of the analytical model is presented, along with its validation by comparison with the results of fully 3D computations.